Changes in quality of life, healthcare use, and substance use in HIV/hepatitis C coinfected patients after hepatitis C therapy: a prospective cohort study. Issue 3 (May 2015) - Yeung, Man Wah; Young, Jim; Moodie, Erica; Rollet-Kurhajec, Kathleen C.; Schwartzman, Kevin; Greenaway, Christina; Cooper, Curtis; Cox, Joseph; Gill, John; Hull, Mark; Walmsley, Sharon; Klein, Marina B.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: Clinical benefits of achieving a sustained virologic response (SVR) with hepatitis c virus (HCV) therapy beyond reducing liver-related outcomes have not been documented in HIV-coinfected patients, who have multiple competing health problems. To gauge the potential benefits of curing HCV in coinfected people, we examined changes in health-related quality of life (HRQOL), healthcare and substance use, and overall mortality after treatment for HCV Coinfection. Design: Prospective multicentre cohort study. Methods: Among patients treated for HCV in the Canadian Coinfection Cohort study, self-reported HRQOL (using the EQ-5D), inpatient and outpatient medical visits, and substance use were assessed before, 6 months and 1 year after completing HCV therapy, comparing SVR-achievers and non-responders. Analysis of covariance and zero-inflated negative binomial regression were used to model the effects of SVR on HRQOL and healthcare use, respectively. Results: Of 1145 patients chronically infected with HCV, 223 (19%) received treatment while under follow-up in the cohort and had HRQOL data collected – 86 (36%) achieved SVR, 68 (29%) did not, 30 (13%) had ongoing treatment, and 39 (17%) had unknown responses. Compared to non-responders, those achieving a SVR had higher HRQOL scores over time (11-unit increase 1 year posttreatment, 95% CI: 2, 21 measured 1 year posttreatment) and a lower rate of health service utilization (adjusted incidence rate ratio: 0.5, 95% CI: 0.3, 0.9). Short-term mortality was low but appeared lower in SVR-achievers (incidence rates: 0.10 vs 0.12 deaths per 100 person-years). However, after successful treatment, a substantial number of patients increased alcohol consumption and continued to inject drugs. Conclusions: Successful HCV treatment results in a range of health benefits for HIV/HCV-coinfected patients. Ongoing substance use, however, may mitigate the short- and long-term benefits associated with curing HCV.